2010
DOI: 10.1159/000289575
|View full text |Cite
|
Sign up to set email alerts
|

Undercarboxylated Osteocalcin Is a Biomarker of Carotid Calcification in Patients with Essential Hypertension

Abstract: The development of vascular calcification is an active, highly regulated process with similarities to bone formation. Osteocalcin (OC), a vitamin K-dependent protein expressed by osteoblasts, contains 3 γ-carboxyglutamic acid residues derived from the vitamin K-dependent posttranslational modification of glutamic acid residues. Circulating undercarboxylated OC (ucOC) is increased in vitamin K deficiency and serum ucOC is reported to be a clinical marker of vitamin K status. Vitamin K deficiency is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 66 publications
(38 reference statements)
2
24
0
Order By: Relevance
“…These data suggest that serum levels of ucOC could be related to CVRF in both HS and T2D patients. These findings agree with the higher ucOC serum levels found by Okura et al[35] in hypertensive patients with carotid calcification than in those without carotid calcification, suggesting that ucOC might be a potential biomarker for carotid artery calcification. Our work also agrees with the results published by Kanazawa et al[23] who found that total serum OC concentration was negatively associated with atherosclerotic parameters (intima-media thickness and ankle-brachial pulse-wave velocity) independent of other CVRF in diabetic men.…”
Section: Discussionsupporting
confidence: 92%
“…These data suggest that serum levels of ucOC could be related to CVRF in both HS and T2D patients. These findings agree with the higher ucOC serum levels found by Okura et al[35] in hypertensive patients with carotid calcification than in those without carotid calcification, suggesting that ucOC might be a potential biomarker for carotid artery calcification. Our work also agrees with the results published by Kanazawa et al[23] who found that total serum OC concentration was negatively associated with atherosclerotic parameters (intima-media thickness and ankle-brachial pulse-wave velocity) independent of other CVRF in diabetic men.…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of CD34 /KDR and CD34 /CD133 / KDR endothelial progenitor cells costaining for osteocalcin has been reported to be significantly increased in patients with severe multi-vessel coronary artery disease as well as those with normal coronary arteries with endothelial dysfunction compared to that observed in control patients 28) . Furthermore, another study reported that the undercarboxylated osteocalcin levels were higher in the common carotid artery calcification group than in non-calcification group among 92 patients with essential hypertension 29) . Collectively, there may be a link between osteocalcin and atherosclerosis and/or vascular calcification.…”
Section: Resultsmentioning
confidence: 96%
“…OC was measured using luminometry in one study (63). ucOC was measured in five studies (22, 31, 32, 41, 44), cOC in one study (44), and total OC was measured in the remaining studies (Table 1). OC positive mononuclear cells, endothelial progenitor cells (EPCs), or osteoprogenitor cells (OPCs) were examined by seven studies (37, 38, 40, 42, 52, 61, 62).…”
Section: Resultsmentioning
confidence: 99%
“…In seven studies that measured ucOC and markers of atherosclerosis or calcification, two positive outcomes were reported (31, 32), three negative outcomes (22, 29), and four non-significant outcomes (41, 44, 60). Fifty-four percent of studies did not adjust for any confounding variables (Table 1).…”
Section: Resultsmentioning
confidence: 99%